High-speed camera-based coefficient of restitution of apple under three-dimensional fruit-to-fruit collision in air for vibration harvesting - Chen, Chi; Wei, Ruiyang; He, Leilei; Xia, Man; Li, Rui; Yang, Liling; Soloviev, Vladimir; Grecheneva, Anastasia; Sahni, Ramesh; Majeed, Yaqoob; et al. (International Journal of Agricultural and Biological Engineering, 2025)
The coefficient of restitution (CoR) is an important parameter for designing vibration-harvesting machinery. There are three main types of fruit-to-fruit collisions during vibration harvesting: collision between fruits collected using a collection device and falling fruits, collision between fruits on branches before being removed, and collision of fruits in the air. The CoR for the first two types of collision was investigated separately using drop and pendulum methods. However, there have been few studies on CoR for the collision of fruits in the air. In this study, a platform was designed to simulate the collision of fruits in the air during vibration harvesting for the ‘Gala’ apple, where influences of collision velocity on CoR were studied. Images from a high-speed camera were processed based on RGB to Lab conversion to extract the bruise surface and calculate the bruise volume. Total bruise volume, the sum of two apple bruise volumes, was calculated and analyzed in relation to the CoR. Results showed that the CoR decreased with collision velocity increasing from 1.0 m/s to 1.4 m/s, where the CoR reached 0.93 or higher when collision velocity was 1.0 m/s, making fruits not bruise, while fruits began to bruise when collision velocity increased from 1.2 m/s. The CoR did not continue to decrease when collision velocity exceeded 1.4 m/s due to rotation. There was little correlation between total bruise volume and the CoR due to the composite motion of fruits in the air, indicating that the CoR may not be an indicator to determine the degree of fruit bruise when the fruit made a composite motion during the collision. Therefore, this research is expected to guide the establishment of a more accurate fruit model to design optimal vibration harvesting machinery. Keywords: coefficient of restitution, three-dimensional displacements, fruit damage, image analysis, rotational motion DOI: 10.25165/j.ijabe.20251804.9192 Citation: Chen C, Wei R Y, He L L, Xia M, Li R, Yang L L, et al. High-speed camera-based coefficient of restitution of apple under three-dimensional fruit-to-fruit collision in air for vibration harvesting. Int J Agric & Biol Eng, 2025; 18(4): 248–253.